Biofilm formation and induction of stress response genes is a common response of several serotypes of the pneumococcus to cigarette smoke condensate. Issue 2 (February 2020) - Cockeran, Riana; Dix-Peek, Thèrése; Dickens, Caroline; Steel, Helen C.; Anderson, Ronald; Feldman, Charles
Summary: Objectives: Exposure to cigarette smoke impacts on the virulence of Streptococcus pneumoniae (pneumococcus) by mechanisms including induction of biofilm formation. Most studies, however, have focused on individual strains of the pneumococcus. Accordingly, the current study has investigated the commonality of the pneumococcal stress response to cigarette smoke condensate (CSC), using five different strains of the pathogen. Methods: Following exposure to CSC at final concentrations of 80 and 160 µg mL −1 during a 16 h incubation period, biofilm formation was measured using a crystal violet-based spectrophotometric procedure. Expression of stress genes seemingly linked to biofilm formation viz. hk11 and rr11 [histidine kinase and response regulator of the two-component regulatory system 11 (TCS11) respectively], cat eff (cation efflux system protein), abc (ATP-binding component of an ATP-binding cassette transporter) and 2005-hyp (hypothetical gene) was measured by sequential extraction of RNA, cDNA synthesis and real-time qPCR. Results: Exposure of all five strains of the pneumococcus to CSC, resulted in significant biofilm formation, as well as induction of all five test stress genes. Conclusions: Augmentation of induction of selective stress genes and biofilm formation are common, possibly linked, responses of various serotypes of the pneumococcus to CSC, favouring both persistence of the pathogen and decreased efficacy of antibiotics.